A Method for the Development of Self-Contained Breathing Apparatus Using Computer Modeling - G. Matveikin, V; N. Tugolukov, E; Yu. Alekseyev, S; Yu. Zakharov, A (International Journal of Engineering and Technology, 2018)
The methodology of designing self-contained breathing apparatus with chemically bound oxygen is considered.The distribution of mass and dimensions of the apparatus along the human body increases the comfort of its use, expands the range of types of operations that a person can perform. The problem of optimal design of apparatuses is formulated. The solution of the problem is provided by the use of automated stands of virtual / augmented reality simulating human breathing and the operation of devices. The work of the stands is based on computer modeling systems implemented on the basis of analytical solutions of systems of differential equations, describing the processes occurring in the apparatus. They function as part of the equipment or synchronously with it. The time of obtaining the result is the same defining characteristic as the accuracy of the result.The design of programs that provide the solution of simulation problems in real time is carried out using the methods of distributed systems, object-oriented programming, parallel computations, and object-oriented modeling. The combination of these methods makes it possible to use a component-oriented architecture. Its use will allow for quick modelling of software systems that implement the solution of the simulation problem, depending on the design of the device being developed.Â Â